2016
DOI: 10.1002/biot.201500628
|View full text |Cite
|
Sign up to set email alerts
|

Production of a tumour‐targeting antibody with a human‐compatible glycosylation profile in N. benthamiana hairy root cultures

Abstract: Hairy root (HR) cultures derived from Agrobacterium rhizogenes transformation of plant tissues are an advantageous biotechnological manufacturing platform due to the accumulation of recombinant proteins in an otherwise largely protein free culture medium. In this context, HRs descending from transgenic Nicotiana tabacum plants were successfully used for the production of several functional mAbs with plant-type glycans. Here, we expressed the tumor-targeting monoclonal antibody mAb H10 in HRs obtained either by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
(79 reference statements)
2
21
0
Order By: Relevance
“…Interestingly, a recent work showed that the treatment of roots expressing mAb M12 with NAA over a prolonged period caused an altered root phenotype, which was characterized by root hair proliferation, elongation and formation of nodular structures . This phenotype was more pronounced in roots induced with a higher concentration of NAA; the same phenomenon was also observed in HR cultures expressing the mAbH10 . Given these evidences, we have generated HR cultures expressing a secretory version of RFP, which then were used as a model system to study protein secretion from roots.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Interestingly, a recent work showed that the treatment of roots expressing mAb M12 with NAA over a prolonged period caused an altered root phenotype, which was characterized by root hair proliferation, elongation and formation of nodular structures . This phenotype was more pronounced in roots induced with a higher concentration of NAA; the same phenomenon was also observed in HR cultures expressing the mAbH10 . Given these evidences, we have generated HR cultures expressing a secretory version of RFP, which then were used as a model system to study protein secretion from roots.…”
Section: Introductionmentioning
confidence: 85%
“…The A. rhizogenes A4 strain carrying the pBIΩ‐2B8‐Fc or pBIΩ‐RFP expression vector was used to transform wild type (WT) N. benthamiana (in the case of RFP) or ΔXTFT N. benthamiana (for 2B8‐Fc) leaf segments as described before . Briefly, recombinant A. rhizogenes A4 was grown in YEB medium to OD600 = 0.5, at 28 °C and 160 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-characterized in vitro propagation, transformation, and maintenance methods of these plants are the factors behind their selection. The protein was expressed in whole plant tissue [66,68,69], leaves [70][71][72][73][74][75], flower [76], seeds [77][78][79][80][81], hairy root culture [82] or tobacco BY-2 (tobacco cultivar Bright Yellow) cells [8,83,84] (Fig. 4).…”
Section: Transformation Methodologies Target Plants and Expression Omentioning
confidence: 99%